Honoring Deceased Donors with a Unique Family-Designed Statement Followed by a Moment of Silence: Effect on Donation Outcomes. (June 2013) - Neidlinger, Nikole; Gleason, Brandy; Cheng, Jing
Context: Studies indicate that donor families and hospital staff, particularly operating room staff, fear that organ donors will not be treated with dignity, honor, and respect. Objective: The ritual of a unique, family-designed statement of honor followed by a 15-second moment of silence in the operating room before organ recovery was implemented to honor organ donors and their families. The purpose of this study was to describe the development of the ritual and to investigate its impact on donation rates in the California Transplant Donor Network's service area. Design: Cross-sectional observational study. Setting: The California Transplant Donor Network, an organ procurement organization. Participants: 58 organ donors and families in 39 donor hospitals. Main Outcome Measures: Variables of interest included hospital rate of referral and of timely referral to their organ procurement organization, collaborative conversion rates, and donor families' response to implementation of the new ritual. Results: The ritual was implemented in 2011 in several randomly selected hospitals locally. Seventy-one unique rituals were performed in 22 local hospitals in the trial period. No families or health care providers declined to participate. Families reported that the ritual honored their loved ones. Although the collaborative conversion rates were similar in hospitals before implementation (2010), implementation of the ritual affected donation rates in 2011. Conclusions: The 15-second moment of silence honors deceased donors and their families and improves donation rates in donor hospitals.